ARCHIVES GOVERNANCE IN SMP NEGERI 6 ONE ROOF DULUPI BOALEMO GORONTALO PROVINCE - Marhaba, Marwan; Juriko Abdussamad; Tui, Fenti Prihatini (Yayasan Nuraini Ibrahim Mandiri, 2024)
The purpose of the study is to analyze and describe the management of school archives. Research uses a qualitative approach, because the qualitative approach utilizes direct data sources in a natural context (natural setting) to reveal various aspects of observed phenomena. The type of research applied is descriptive research that aims to conduct an in-depth analysis of the situation and conditions of a particular phenomenon. The results showed that archive management at SMP Negeri 6 Satu Atap Dulupi still has many obstacles. From the policy specs, there are still limited human resources specifically in the field of archives, lack of understanding of records management among teachers, and poorly structured organization of archives causing records management to be ineffective. Furthermore, looking at the determinants of records management, the results of the study show that financial management is not optimal, limitations of digital management, limitations of physical storage, and lack of a structured management system. Increased understanding, utilization of technology, the role of stakeholders, more focused supervision, and increased structuring in managing archives are needed to increase their efficiency and effectiveness.